Microwave Technology Using Low Energy Concentrated Beam for Processing of Solid Waste Materials from Rapana thomasiana Seashells - Sorin Vasile Savu; Daniela Tarnita; Gabriel Constantin Benga; Ilie Dumitru; Iulian Stefan; Nicolae Craciunoiu; Adrian Bebe Olei; Ionel Danut Savu (Energies, 2021)
The solid waste of Rapana thomasiana seashells both from domestic activities and natural waste on seashore can be used to obtain viable products for medical applications. However, conventional technologies applied for sintering the materials require massive energy consumption due to the resistance heating. Microwave heating represents an advanced technology for sintering, but the stability of the process, in terms of thermal runaway and microwave plasma arc discharge, jeopardizes the quality of the sintered products. This paper aims to present the results of research focused on viable heating technology and the mechanical properties of the final products. A comparative analysis, in terms of energy efficiency vs. mechanical properties, has been performed for three different heating technologies: direct microwave heating, hybrid microwave heating and resistance heating. The results obtained concluded that the hybrid microwave heating led to final products from Rapana thomasiana solid waste with similar mechanical properties compared with resistance heating. In terms of energy efficiency, the hybrid microwave heating was 20 times better than resistance heating.